2022
DOI: 10.1007/s11332-022-00997-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of electromyography during 2000 m rowing ergometry

Abstract: Purpose This study aimed to investigate the reliability of surface electromyography (EMG) assessed at seven muscles during three repeated 2000 m rowing ergometer sessions. Methods Twelve male well-trained rowers participated in a repeated measures design, performing three 2000 m rowing ergometer sessions interspersed by 3–7 days (S1, S2, S3). Surface electrodes were attached to the gastrocnemius, biceps femoris, gluteus maximus, erector spinae, vastus medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Our study is the first to analyze the changes in EMG activity using multiple indicators from different distance points during a 2000 m rowing ergometer test. Gee et al [16] investigated the reliability of EMS assessed in seven muscles during three repeated 2000 m rowing ergometer tests and reported that the reliability of EMG values over repeated 2000 m was generally "acceptable" although EMG seemed not sensitive enough to detect potential changes concerning changes in pacing strategy. We hypothesized that the lack of sensitivity of EMG could be related to the results calculated by mean 500 m raw EMG signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is the first to analyze the changes in EMG activity using multiple indicators from different distance points during a 2000 m rowing ergometer test. Gee et al [16] investigated the reliability of EMS assessed in seven muscles during three repeated 2000 m rowing ergometer tests and reported that the reliability of EMG values over repeated 2000 m was generally "acceptable" although EMG seemed not sensitive enough to detect potential changes concerning changes in pacing strategy. We hypothesized that the lack of sensitivity of EMG could be related to the results calculated by mean 500 m raw EMG signals.…”
Section: Discussionmentioning
confidence: 99%
“…The EMG electrodes were attached to three muscle sites from the right side of the body muscles vastus medialis (VAM), erector spinae (ERS) and latissimus dorsi (LD). These muscle sites have been previously shown to play an important role in rowing techniques [11,16]. Before fixing the electrodes, the skin was shaved and cleaned with alcohol to minimize the impedance.…”
Section: Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation